Pelatihan Pembuatan dan Pengelolaan Media Pembelajaran Berbasis Web-Blog pada Mahasiswa Semester VI Program Studi PGMI STKIP Nurul Huda OKU Timur - Andini, Nesi Anti; Hasan, Sholeh (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2019)
The importance of learning objectives requires the use of appropriate media so that learning runs effectively and efficiently. The learning media is very important in supporting the learning process and is often overlooked by teachers for various reasons, including limited time, difficulty finding the right media, and also limited funds. With a variety of IT-based and service devices, lecturers and students can access them online and there are applications that make it free for users. Among them are blog users as learning media. This community service activity aims to introduce information and communication technology in the form of Web-Blogs that will later help students who will be prepared to become teacher candidates to modify learning media. The implementation of community service in general can be categorized as successful in terms of participant participation. Participants felt that this dedication activity was very useful for developing web-blog-based learning media that they would use in later learning. The participants' responses to the service activities carried out stated that from the quality of the speakers, the quality of the modules was very good.